Development of Student Worksheets Based on Scientific Literacy for High School - Syafitri, Dinda; Anas, Nirwana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine the validity, practicality, and effectiveness of LKPD based on scientific literacy. The research method uses development or R&D, which is applied to the 4D model, which includes Define, Design, Develop, and Disseminate. Sources of data were obtained through questionnaires or distributed questionnaires to determine validation and practicality tests, while data obtained through pretest and posttest were used to determine the effectiveness analysis of the developed LKPD. Data analysis techniques use quantitative methods, namely by calculating using Likert scale values and N-gain. The population in this study were 30 students of class X IPA 1 at Prima Tembung Private High School. The sampling used in this study is probability sampling, where every student has the same opportunity. The validity test of LKPD is used to evaluate the developed LKPD, which is measured using instruments in the form of validation from media experts and material experts. The results of the practical test for teacher and student responses were 75% and 79.62%, respectively, indicating that LKPD was very practical. The analysis of the LPKD effectiveness test was obtained through an N-gain score of 0.44 in the moderate category in improving students' scientific literacy abilities. Thus, scientific literacy-based LKPD on ecosystem material for class X high school developed by researchers proved to be valid, practical, and effective.